Cyclopes do not cultivate (Teología, 2019)
Cyclops’ island (Odyssey IX) is visited in order to peer into the origins of our culture. Polyphem is like an inverted mirror: it turns upside down our images of a cultivated land, a cultivated man, a cared- for living together.
Keywords: Culture; Analogical Hermeneutics; Method.